Virtual Reality-Based Anatomy Learning: A Sustainable Alternative to Cadaveric Dissection in Medical Education - Hasti, Novrini; Sitanggang , Andri Sahata; Syafariani, R Fenny; Sari, Febilita Wulan; Pangaribuan, Imelda; Wahyuni, Wahyuni; Radliya, Nizar Rabbi; Susanti, Sussy; Gradiansyah, Aqbil (Proceeding of International Conference on Informatics, Engineering, Science & Technology, 2025)
This quasi-experimental study aimed to compare the effectiveness, cost-benefit, and long-term knowledge retention of VR-based anatomy instruction versus traditional cadaveric dissection. We randomized 300 preclinical medical students to VR (n=150) or cadaveric instruction (n=150). Validated knowledge tests, engagement scales, and cost metrics were administered immediately post-intervention and at 3- and 6-month follow-ups. VR yielded higher immediate post-test scores (78.6 ± 9.2 vs 74.3 ± 8.7; p